Health Workers' Competence in Home Blood Pressure Measurement-Based Hypertension Management in a Remote Border Region of Indonesia - Pius AL Berek; Maria Paula Marla Nahak; Maria Fatimah W. A. Fouk (Talenta Publisher, 2026)
Home Blood Pressure Measurement (HBPM), although strongly recommended for optimizing hypertension control and identifying white-coat and masked hypertension, remains suboptimally implemented in rural and resource-constrained border settings, primarily due to limited competence among frontline health workers. This study aimed to assess health workers’ competence related to HBPM-based hypertension management in a remote border region of Indonesia. A cross-sectional study was conducted among 331 health workers, including nurses, midwives, physicians, pharmacists, and allied health professionals. A validated 21-item questionnaire assessed three HBPM knowledge domains: fundamental concepts, clinical benefits, and technical implementation. Data were analyzed using descriptive statistics, chi-square tests, and multivariate logistic regression. Overall, 58.0% of participants demonstrated good HBPM-related knowledge. Knowledge scores were highest in the clinical benefits domain, while technical implementation showed the lowest performance. Only 14.8% correctly identified differences between home and clinic blood pressure values, and 26.6% recognized the need to discard first-day readings. Nurses (AOR = 3.5; 95% CI: 1.07–11.53) and midwives (AOR = 5.1; 95% CI: 1.44–18.15) were significantly more likely to have good knowledge compared to other professions. Gender and education level were not significant predictors. Although general awareness of HBPM among health workers was adequate, substantial gaps in technical knowledge persist. Strengthening practical HBPM training, particularly for nurses and midwives as frontline providers, is essential to improve hypertension management in underserved border regions. Keyword: Border region, Health workers, Home blood pressure measurement, Hypertension, Low-resource settings